El rol de los profesionales de la salud en la atención primaria en salud (APS) (2015)
ABSTRACT: This paper presents a critical review of the role of health professionals in primary health care. Methodology: narrative review concepts of primary health care, their connections with different models of health, the role of the health team in both the Primary Health Care and its various approaches. The revision expands the functions of the healthcare professional in this field and the general practitioner, in particular, as well as their actions and training. Discussion: it is argued from some questions about what the role of health professionals in the system and the role it should play in primary care and the organization of health services. It is particularized in the Colombian health system and the emphasis is on the change that is required of the general practitioner, historically linked to the clinic and the hegemony of the biomedical model. Conclusion: a sketch is presented of the formation to the new realities and demands at the present time, three-dimensional macro, meso and micro levels of the socio healthcare.